Role of a Novel Functional Variant in the PPP2R1A Promoter on the Regulation of PP2A-Aalpha and the Risk of Hepatocellular Carcinoma - Chen, Hui-Feng (Public Library of Science, 2013)
Previously, we identified the genetic variant −241 (−/G) (rs11453459) in the PP2A-Aα gene (PPP2R1A) promoter and demonstrated that this variant influences the DNA-binding affinity of nuclear factor-kappa B (NF-κB). In this study, we further confirmed that the transcriptional activity of PPP2R1A may be regulated by NF-κB through the functional genetic variant −241 (−/G). Moreover, we also demonstrated that the methylation status of CpG islands in the promoter of PPP2R1A influences the activity of this gene promoter. Few studies have examined the role of this −241 (−/G) variant in genetic or epigenetic regulation in hepatocellular carcinoma (HCC). To investigate whether this functional variant in the PPP2R1A promoter is associated with the risk of HCC and confirm the function of the −241 (−/G) variant in the HCC population, we conducted a case-control study involving 251 HCC cases and 252 cancer-free controls from a Han population in southern China. Compared with the −241 (−−) homozygote, the heterozygous −241 (−G) genotype (adjusted OR  = 0.32, 95% confidence interval (CI)  = 0.17–0.58, P<0.001) and the −241 (−G)/(GG) genotypes (adjusted OR  = 0.38, 95% CI  = 0.22–0.67, P  = 0.001) were both significantly associated with a reduced risk of HCC. Stratification analysis indicated that the protective role of −241 (−G) was more pronounced in individuals who were ≤ 40 years of age, female and HBV-negative. Our data suggest that the transcriptional activity of PPP2R1A is regulated by NF-κB through the −241 (−/G) variant and by the methylation of the promoter region. Moreover, the functional −241 (−/G) variant in the PPP2R1A promoter contributes to the decreased risk of HCC. These findings contribute novel information regarding the gene transcription of PPP2R1A regulated by the polymorphism and methylation in the promoter region through genetic and epigenetic mechanisms in hepatocarcinogenesis.